Ostensive addressing as an approach in the Tshivenda translation dictionaries: an analysis - Malange, Sheya Alfred (My University, 2010)
Pictures play a role in dictionaries as they show what a particular object looks like. African languages do not always have readily available translation equivalents for some of the English words, and also, English does not always have translation equivalents for Tshivenda cultural bound words. The study has been undertaken to try to solve the problem of lack of equivalents when English and Tshivenda are used as the treated languages in a bilingual dictionary. The study discovered that lexicographers of Tshivenda-English and English-Tshivenda dictionaries do not always give direct and appropriate translation equivalents for English scientific and technological terms in Tshivenda and translation equivalents for Tshivenda cultural bound words. The study found that these lexicographers end up giving transliteration of scientific and technological terms and even a mere borrowing of Tshivenda cultural terms as translation equivalents. In this case the study recommends that Ostensive addressing be introduced in Tshivenda – English and English – Tshivenda bilingual dictionaries as a solution to the problem of lacking equivalents and that pictures not be used excessively but only where necessary and be given immediately after the lemma in the microstructure of a dictionary.
Thesis (M.A. (African Languages)) --University of Limpopo, 2005
Keywords: Thsivenda language translation; African languages; Translating and interpreting; Lexicography